PENGARUH PROGRAM RETINA (REMAJA ANTI NARKOBA DAN KEKERASAN) TERHADAP KEPATUHAN TATA TERTIB SEKOLAH PESERTA DIDIK SMP NEGERI 8 BANDAR LAMPUNG - Destri Zadia Arini; Berchah Pitoewas; Nurhayati; Devi Sutrisno Putri; Lisa Retno Sari (STKIP Subang, 2026)
This study aims to determine the effect of the RETINA Program (Youth Anti-Drugs and Violence) on students’ compliance with school rules at SMP Negeri 8 Bandar Lampung. This research used a quantitative approach with an ex post facto method. The population of this study consisted of 774 students, with a sample of 89 respondents determined using the simple random sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, and were supported by interviews and documentation to strengthen the research data. The collected data were analyzed using simple linear regression analysis with the help of the SPSS program. The results of the study indicate that the RETINA Program has a positive and significant effect on students’ compliance with school rules. Based on the results of the simple linear regression test in the Model Summary table, the coefficient of determination (R Square) value obtained was 0.361. This value indicates that the RETINA Program contributes 36.1% to students’ compliance with school rules, while the remaining 63.9% is influenced by other factors outside the research variables. The RETINA Program plays a preventive and educational role in increasing students’ awareness and compliance with school regulations, thereby supporting the creation of an orderly, safe, and conducive school environment.